A regime shift in North Pacific annual mean sea surface temperature in 2013/14 - Xiao, Dong; Ren, Hong-Li (Frontiers in Earth Science, 2023)
This study revealed a new regime shift in the North Pacific annual mean sea surface temperature (SST) in 2013/14, robust in multiple SST data sets. This regime shift shows a horseshoe pattern with warming SST along the North America western coast and toward the Central Pacific. It suggests a phase reversal of the Victoria Mode (VM) and it seems unrelated to shift in the Pacific Decadal Oscillation (PDO) and Interdecadal Pacific Oscillation (IPO). Associated with this regime shift, the annual surface air temperature significantly enhanced over the high-latitude landmass after 2014, whereas declined over the northeastern Canada and southwestern Greenland. The annual precipitation generally increased (decreased) in the Northern (Southern) Hemisphere landmass monsoon regions. There are no regime shifts in Equatorial Central-East Pacific SST and the intensity and locations of the Aleutian Low around 2013/14. These facts suggest the regime shift of North Pacific SST in 2013/14 may not originate from the decadal variations of midlatitude atmosphere and tropical ocean. The extensive influence of this regime shift in 2013/14 on the atmospheric, oceanic and ecological systems warrants further investigation.